THE USE OF EMBEDDED ADVERTISEMENTS IN FOREIGN MOVIES - SALMAN, IMAN ABBAS; MALIK, HUDA (ALBAHITH ALALAMI, 2021)
Embedded advertisement constitutes a special kind of communication. As it performs many important roles such as giving information, highlighting the value of the product, and urging the target consumer to buy it by influencing his/ her behavior using an attractive manner of mind and conscience. Both cinema and television are the most prominent and powerful advertising media that enjoy the interest of all audiences and capture most of the advertising spending. As advertisers have paid attention to the importance of indirectly incorporating their products into content that the audience loves and is keen to follow, since the actual impact lies in the inclusion of the product within content that the audience appeals to. Hence, this leads to influence the product indirectly. This is what is known as embedded advertisement. The problem of our research can be defined by the main question (What is meant by embedded advertisement and how to employ practical techniques or elements of cinematic film in making embedded advertisement within foreign films that have won the Oscar?). The significant of the study stems from studying embedded advertisements in films, and how to pass products tacitly into films. Therefore, this research aims to identify the embeddedadvertisementsandreveal how the techniques or artistic elements used in making the implicit advertisement are employed within foreign films that have won the Oscar. The researcher used the survey method, and she used a content analysis tool to identify the embedded advertisements included in foreign films that won the Oscar Award. The study reached several results, the most important of which is (that the embedded advertisements that appeared in the films adopted the methods of displaying the embedded advertisement in the visual and written style, in order to ensure that the advertising message reaches the recipient clearly and to give a clear picture of the advertised product.In addition to that, the dazzling element present in the films under study, such as sound, image, movement, and story... All these factors provide an attractive atmosphere and attract attention to the product that is included within the events of the film).